ENGLISH LANGUAGE LEARNING ENJOYMENT AMONG INDONESIAN UNDERGRADUATE STUDENTS: SOCIAL INTERACTION IN ENGLISH SPEAKING LEARNING - Wahyuni; Dayat, Dayat; Meliasari, Rahayu (Program Studi Pendidikan Bahasa Inggris, 2025)
ABSTRACT This study investigates the relationship between Foreign Language Enjoyment (FLE) and social interaction among Indonesian undergraduate students in English-speaking classes. It also explores whether the duration of learning English affects students’ level of social interaction. The study employs a quantitative descriptive design using a Likert-scale questionnaire adapted from the Foreign Language Enjoyment Scale by Dewaele and MacIntyre (2014). Data were collected from 91 English Education students from various universities in Indonesia. The findings reveal that students generally experience moderate to high levels of FLE, particularly when the classroom environment is supportive and interactive. Pearson correlation analysis shows a positive and significant relationship between FLE and social interaction, indicating that students who enjoy learning English are more likely to participate actively in class. However, regression analysis reveals that the duration of English learning does not significantly influence students’ social interaction. These results suggest that emotional and social classroom factors, such as teacher support, peer collaboration, and classroom engagement, play a more influential role in encouraging interaction than the number of years spent studying English. The study supports the socio-constructivist theory, which emphasizes the importance of meaningful communication and a positive learning environment in foreign language learning. Keywords: Foreign Language Enjoyment, Social Interaction, English Learning Duration, English-Speaking Class, Indonesian Students